Maximizing Data Coverage through Eight Sequential Mass Spectrometry Images of a Single Tissue Section - Seeley, Erin H. (Journal of the American Society for Mass Spectrometry, 2025)
Typical mass spectrometry imaging (MSI) experiments involve the collection of data from only one class of molecules per section. However, it is often necessary to collect data from different classes of analytes from the same biopsy, and generally, serial sections are used for additional analyte classes. However, differences will be observed between the cells present in each section, especially if the sections are not immediately serial with each other. In this study, a method is presented that allows for 8 mass spectrometry images to be collected sequentially from the same tissue section, including metabolites in positive and negative mode, lipids in positive and negative mode, N-linked glycans, O-linked N-acetylglucosamine, small intact proteins, and tryptic peptides. The order of data collection allows for washing to be used that removes analytes already detected and enhances the signal of subsequently imaged analytes. The collection of multiple images from the same tissue section enables facile coregistration of multiple data sets for evaluation of co- and differential localization across molecular classes.